Role of Anxiety Sensitivity, Intolerance of Uncertainty, and Cyberchondria Behaviors among Individuals Diagnosed with COVID-19 : Role of Anxiety Sensitivity and Cyberchondria Behaviors - Rashid, Nudrat; Shahid, Amna; Munir, Mehwish; Khan, Muhammad Umar; Ramzan, Zoobia (Pakistan Journal of Health Sciences, 2023)
The COVID-19 pandemic was a quick outbreak that affected individuals’ mental health. Objective: To investigate the relationship between anxiety sensitivity, intolerance of uncertainty, and cyberchondria tendencies among individuals with and without COVID-19. Methods: A total of 411 COVID-19 individuals, including 185 men (45%) and 226 women (55%) from low, middle, and high socioeconomic statuses (103 men (25.1%), 155 men (37.7%), and 153 men (37.2%)) were recruited. The participants ranged in age from 18 to 30. Data were collected from different public sector hospitals and a public sector university of Faisalabad. We calculated the results through SPSS version 27. Results: The findings showed a significant positive association between cyberchondria tendencies and anxiety sensitivity (r = 0.61, p.001) and intolerance for uncertainty (r = 0.64, p.001). Moreover, significant differences were observed in the variable of anxiety sensitivity (t =-10.40, p.001), intolerance of uncertainty (t = -5.89, p.001), and cyberchondria tendency (t =-6.08, p.001) between individual diagnosed with and without COVID-19. Conclusions: It is concluded that there is a significant relationship of anxiety sensitivity and intolerance of uncertainty with cyberchondria tendencies and significant differences were found between gender and individuals diagnosed with and without COVID-19